Information dissemination and fairness perceptions: The case of Inland Revenue Board Malaysia - Saad, Natrah (2012)
This paper highlights how information dissemination or information sharing between the authority (in this case, is the Inland Revenue Board Malaysia-IRBM) and the community at large would to certain extent influence their perceptions on the fairness of the income tax system.Specifically, this paper investigates perceptions of individual taxpayers on the fairness of the income tax system in Malaysia and how such perceptions were formed, by applying a mixed method (through survey and interview).The survey involved 852 respondents while the interview sessions were conducted on 30 participants. The descriptive analysis and thematic analysis were carried out on survey data and interview data, respectively. Survey results indicate that taxpayers generally perceive the income tax system as fair.The interviews, on the other hand, showed that taxpayers were not happy with government spending of tax revenue.Such view was actually resulted from the lack of information disclosed by the IRBM on how they have used the taxpayers’ money. Taxpayers believed if such dissemination of information has taken place, their views on IRBM’s credibility may have been improved.